B-Cell Homeostasis Is Maintained During Two Months of Head-Down Tilt Bed Rest With or Without Antioxidant Supplementation - Bonnefoy, Julie; Baselet, Bjorn; Moser, Dominique; Ghislin, Stéphanie; Miranda, Silvana; Riant, Elodie; Vermeesen, Randy; Keiler, Annekathrin M.; Baatout, Sarah; Choukér, Alexander; Frippiat, Jean-Pol (Frontiers in Immunology, 2022)
Alterations of the immune system could seriously impair the ability to combat infections during future long-duration space missions. However, little is known about the effects of spaceflight on the B-cell compartment. Given the limited access to astronaut samples, we addressed this question using blood samples collected from 20 healthy male volunteers subjected to long-duration bed rest, an Earth-based analog of spaceflight. Hematopoietic progenitors, white blood cells, total lymphocytes and B-cells, four B-cell subsets, immunoglobulin isotypes, six cytokines involved in inflammation, cortisone and cortisol were quantified at five time points. Tibia microarchitecture was also studied. Moreover, we investigated the efficiency of antioxidant supplementation with a cocktail including polyphenols, omega 3, vitamin E and selenium. Our results show that circulating hematopoietic progenitors, white blood cells, total lymphocytes and B-cells, and B-cell subsets were not affected by bed rest. Cytokine quantification suggested a lower systemic inflammatory status, supported by an increase in serum cortisone, during bed rest. These data confirm the in vivo hormonal dysregulation of immunity observed in astronauts and show that bed rest does not alter B-cell homeostasis. This lack of an impact of long-term bed rest on B-cell homeostasis can, at least partially, be explained by limited bone remodeling. None of the evaluated parameters were affected by the administration of the antioxidant supplement. The non-effectiveness of the supplement may be because the diet provided to the non-supplemented and supplemented volunteers already contained sufficient antioxidants. Given the limitations of this model, further studies will be required to determine whether B-cell homeostasis is affected, especially during future deep-space exploration missions that will be of unprecedented durations.